Character Development Model for Kindergarten Students Based on the Pancasila Student Profile Strengthening Project (P5) in Mataram, Indonesia - Yumna Arifamahira; Windy Rahmania Octaviani; Afina Rosmalia; Baiq Wike Pratamaswari; Bq. Ulan Saswari Aji; Lalu Sumardi (Lafadz Jaya Publisher, 2024)
The importance of character education in early childhood cannot be ignored because this phase is the